2021
DOI: 10.1038/s41598-021-91450-6
|View full text |Cite
|
Sign up to set email alerts
|

A novel mineralocorticoid receptor antagonist, 7,3',4'-trihydroxyisoflavone improves skin barrier function impaired by endogenous or exogenous glucocorticoids

Abstract: Excess glucocorticoids (GCs) with either endogenous or exogenous origins deteriorate skin barrier function. GCs bind to mineralocorticoid and GC receptors (MRs and GRs) in normal human epidermal keratinocytes (NHEKs). Inappropriate MR activation by GCs mediates various GC-induced cutaneous adverse events. We examined whether MR antagonists can ameliorate GC-mediated skin barrier dysfunction in NHEKs, reconstructed human epidermis (RHE), and subjects under psychological stress (PS). In a preliminary clinical in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 51 publications
(61 reference statements)
0
4
0
Order By: Relevance
“…A recent study extended the implication of GC-induced off-target MR activation in skin defects associated with psychological stress, acting through an increase in endogenous GC cortisol levels, which alters epidermal barrier function and worsens several common skin diseases, such as atopic dermatitis or psoriasis (Lee et al, 2021). This study showed that MR antagonism improved the deleterious consequences of GC on skin barrier function found in normal human epidermal keratinocytes and reconstructed human epidermis (Lee et al, 2021). Importantly, we observed in a previous study that Clobetasol pretreatment of mouse skin leads to an increased expression in the wound of epithelial sodium channels (ENaC), a target gene downstream of MR activation, that was blunted when the wound was treated with the MR blocker Canrenoate.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…A recent study extended the implication of GC-induced off-target MR activation in skin defects associated with psychological stress, acting through an increase in endogenous GC cortisol levels, which alters epidermal barrier function and worsens several common skin diseases, such as atopic dermatitis or psoriasis (Lee et al, 2021). This study showed that MR antagonism improved the deleterious consequences of GC on skin barrier function found in normal human epidermal keratinocytes and reconstructed human epidermis (Lee et al, 2021). Importantly, we observed in a previous study that Clobetasol pretreatment of mouse skin leads to an increased expression in the wound of epithelial sodium channels (ENaC), a target gene downstream of MR activation, that was blunted when the wound was treated with the MR blocker Canrenoate.…”
Section: Discussionmentioning
confidence: 97%
“…Biyashev et al recently reported that the association of vitamin D3 and the MR antagonist spironolactone improves the inflammation shift and therefore enhances wound healing induced by nitrogen mustard exposure (Biyashev et al, 2020 ). A recent study extended the implication of GC‐induced off‐target MR activation in skin defects associated with psychological stress, acting through an increase in endogenous GC cortisol levels, which alters epidermal barrier function and worsens several common skin diseases, such as atopic dermatitis or psoriasis (Lee et al, 2021 ). This study showed that MR antagonism improved the deleterious consequences of GC on skin barrier function found in normal human epidermal keratinocytes and reconstructed human epidermis (Lee et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GR tethering to AP‐1 also is implicated in negative feedback effects of glucocorticoids on CRH (Malkoski & Dorin, 1999), as well as through GR monomer binding to negative GREs, and this may provide a common mechanism to explain the lack of effects of 5αTHB on collagen integrity and the HPA axis. It is also possible that alternative receptors may be involved; for example, MR antagonists can alleviate glucocorticoid‐driven skin atrophy (Bigas et al, 2018; Lee et al, 2021; Maubec et al, 2015; Sevilla et al, 2020; Sevilla & Perez, 2018).…”
Section: Discussionmentioning
confidence: 99%